O impacto do Mindfulness na adesão ao tratamento para perda de peso em mulheres inférteis e portadoras de síndrome dos ovários policísticos com sobrepeso ou obesidade - Edna Mariz Camara Sant Anna (2016)
The aim of this study is to evaluate the impact of Mindfulness on compliance to the treatment for weight loss in obese and overweight women with infertility and polycystic ovary syndrome (PCOS). More specifically, it assesses the effects of this therapy on compliance to diet and exercise, such as the variation in body mass index (BMI) in these women. It also measures the effect of Mindfulness on stress, wellbeing, and quality of life of these women through the score of Psychological General Well-Being Index (PGWBI) questionnaire. This study was conducted as a 2-arms randomized controlled trial. Ninety participants were recruited from the Human Reproduction Laboratory Professor Aroldo Fernando Camargos in the Hospital das Clinicas, UFMG, and were randomly assigned to the mindfulness intervention group (n=51) or to the control group (n=49). In both groups there was a drop of participants, leaving the final analysis to 28 women in the intervention group and 24 in the control group. Change in weight, body composition and waist circumference were the initial indicator of adherence to the weight loss program. The intervention group participated in the mindfulness program of 8 weekly sessions of 2 hours each. All participants provided written informed consent for participation in the study. RESULTS: There was a mean reduction of 1.8 kg in the intervention group (p = 0.002) and mean reduction of 1.0 kg in the control group (p = 0.022). The BMI reduction was significant in both groups. Neither weight reduction nor BMI reduction differed quantitatively between the intervention group and the control group. However, there was an average reduction of 1.5 cm of waist circumference (p = 0.007) and 2.0 cm of hip circumference (p = 0.002) in the intervention group, while in the control group, the average reduction in waist circumference was 0.8 cm (p = 0.633) and 0.3 cm the circumference hip (p=0.100). The intervention group also showed a significant improvement in quality of life (p=0.001). The same did not occur in the control group (p=0.829). These findings suggest that mindfulness may be an effective intervention to increase the levels of adherence to the treatment for weight loss and improvement of quality of life.